The activity space of travel behavior: Research opportunities for geography studies in Indonesia - Shalihati, Sakinah Fathrunnadi (American Institute of Physics Inc., 2023)
The interaction between the desire to meet the needs of individuals/groups with the destination location and the quality of the current transportation infrastructure results in travel behavior. Activity space is the movement space that contains numerous coordinates of the locations visited in a travel behavior for a set period. Space is classified as one of the relative spaces in geography, and it can be identified by size and shape through operational space based on perception. The operational strategy of activity space has been extensively developed by researchers outside of Indonesia, as well as in empirical testing, but it is still underexplored in Indonesia. The article aims is to identify research opportunities in operating the activity space using a geographic strategy, as well as to demonstrate these potentials utilizing shared events among the terms included. Literature review and bibliometric network data analysis were employed as the method of this study. The findings reveal that different types of methods are used to operate the activity area and that there are still contribution chances to alter existing approaches using a geographic perspective. This is supported by evidence from bibliometric research, which shows that the co-occurrence of terms in the keywords of the contribution ideas still has the potential to be included in a series of publications. © 2023 Author(s).